Innate-like self-reactive B cells infiltrate human renal allografts during transplant rejection - Yuta Asano (Nature Portfolio, 2021)
Intrarenal B cells are indicative of poor prognosis in human renal allografts. Here the authors use single cell RNA sequencing to examine how intrarenal B cells contribute to renal rejection and find a population of innate B cells reactive to renal-specific or inflammation-associated antigens.